Welcome to the Ocean of Research across Technical Disciplines - Mishra, Anjay Kumar (Journal of UTEC Engineering Management, 2023)
This editorial introduces the inaugural issue of the Journal of UTEC Engineering Management (JUEM), which aims at disseminating research and innovation in wide technical and managerial disciplines. It starts with a background and need to the journal suggests their potential readers, and concludes with a justification on the suitable development of journal name which focuses broad area of innovative research from different disciplines on technical researchable issues. This journal has started the new approach of publications in context of Nepal with a view to promote open access publication and copyright will be with authors. That signifies the author to obtained intellectuals property rights on their own name. This journal is an official publication of United Technical College, Affiliated to Pokhara University. It confers high quality academic publication through blind peer reviewed. This issues contains articles from Nepal and abroad across the field of project management, concrete technology, human resource management, technology management, procurement management and many more. Acknowledging the individuals and institutions involved in bringing the journal from its conception to fruition, the review ends with a call on researchers and practitioners to cross over disciplinary boundaries and create an international platform for intellectual exchange that can lead to positive change in the society scientific